An experimental study on flame geometry in wind-blown pool fires and a new dimensionless parameter. (February 2022) - Ji, Jingwei; Li, Fuqing; Lu, Wen; Sun, Rongyu; Wang, Keyi; Cao, Yin
Abstract: In order to study the relationship between wind speed and such combustion characteristics as pool fire flame length, tilt angle, combustion mass loss rate and heat release rate, a small round diesel pool fire with wind-blown experimental platform was built. The wind speed was 0–1 m/s and the oil pan diameters were 0.218 m, 0.175 m and 0.13 m, respectively. A new dimensionless parameter H r is defined to describe the effects of buoyancy, initial momentum and horizontal wind force on flame length and tilt angle. The results show that when 0 < H r < 0.33, horizontal wind can enhance flame length. When H r ≥ 0.33, it exerts a suppressive effect on flame length. A prediction model of the relation between flame length, tilt angle and H r is introduced. In addition, an expression of flame tilt angle in relation to dimensionless wind speed u *, as well as the empirical equations of mass loss rate and heat release rate of pool fire in relation to horizontal wind speed was obtained experimentally.